Lithium ion battery and electric device
By using oxide solid electrolytes and specific additives in lithium-ion batteries, a low-temperature ion transport network and a protective interface film are constructed, solving the problems of insufficient high-temperature and low-temperature cycle performance and safety performance of lithium-ion batteries, and achieving high safety and long-term cycle stability of the battery.
Patent Information
- Application Number
- CN202511969215.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-03-17
AI Technical Summary
Existing lithium-ion batteries have shortcomings in high-temperature and low-temperature cycle performance and safety performance. Existing modification strategies are difficult to improve structural stability, interface compatibility and safety performance simultaneously.
An oxide solid electrolyte is used to mix the positive electrode and coat it with a membrane. By combining fluorosulfonamide and mannitol carbonate sulfate additives, and by precisely controlling the coating thickness, additive ratio and electrolyte volume, a low-temperature ion transport network is constructed to improve thermal stability and dendrite suppression ability, and a protective interface film is formed to optimize high-temperature cycling.
It achieves a balance between high battery safety, good low-temperature discharge characteristics and high-temperature long-cycle stability, reduces electrolyte usage, and enhances overall application value.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a lithium-ion battery and an electrical device thereof. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, low self-discharge, and long cycle life, are widely used in electronic devices and new energy vehicles. Their operation relies on the synergistic effect of the positive electrode, negative electrode, electrolyte, and separator. The positive electrode material has a significant impact on the overall performance of the battery. Under charge-discharge cycles and high-temperature conditions, mainstream products may experience problems such as cycle performance degradation due to structural distortion, increased internal resistance and energy loss caused by interfacial side reactions, and safety hazards related to thermal runaway.
[0003] Among existing modification strategies, doping can improve the structural stability of materials to some extent, but its effect on suppressing interfacial side reactions is limited; core-shell structure design suffers from complex preparation processes, easy shedding of the coating layer during cycling, and high production costs; electrolyte optimization can alleviate some interfacial problems, but cannot fundamentally solve the contradiction of structural instability of the cathode material itself. Various single modification strategies are unable to simultaneously improve structural stability, interfacial compatibility, and safety performance, failing to meet the practical application needs of the current energy storage field.
[0004] Therefore, there is an urgent need for a lithium-ion battery and power device that combines structural stability, interface compatibility, and safety and reliability. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to address the poor high-temperature and low-temperature cycle performance and safety performance of lithium-ion batteries in the prior art, and to provide a lithium-ion battery and power device.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: A lithium-ion battery is provided, comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode includes a positive electrode active material layer, the positive electrode active material layer comprising a positive electrode active material and an oxide solid electrolyte. At least one side surface of the separator is coated with an oxide solid electrolyte coating. The electrolyte includes a first additive and a second additive. The first additive includes a fluorosulfonamide compound, and the second additive includes mannitol carbonate sulfate. The first additive has a mass percentage A% of 3%~45% in the electrolyte, the second additive has a mass percentage B% of 0.5%~5% in the electrolyte, the thickness Hµm of the oxide solid electrolyte coating on the separator is 0.5µm~5µm, the mass percentage X% of the oxide solid electrolyte in the positive electrode active material layer is 0.5%~5%, and the liquid retention coefficient Pg / Ah of the lithium-ion battery is 0.8g / Ah~2.5g / Ah. The lithium-ion battery satisfies the following relationship: Equation 1: 0.8 ≤ (H+X) / P ≤ 8; Equation 2: 0.75≤(A+B) / (H+X)≤20; Equation 3: 0.16 ≤ H / X ≤ 6.43; Equation 4: 1.25≤A / B≤36.
[0007] Optionally, the lithium-ion battery satisfies at least one of the following relationships: Equation 5: 1≤(H+X) / P≤5.33; Equation 6: 1.67≤(A+B) / (H+X)≤15.67; Equation 7: 0.4 ≤ H / X ≤ 5; Equation 8: 1.5 ≤ A / B ≤ 30.
[0008] Optionally, the lithium-ion battery satisfies at least one of the following conditions: (1) The mass percentage A% of the first additive in the electrolyte is 10%~30%; (2) The mass percentage (B%) of the second additive in the electrolyte is 1% to 3%; (3) The thickness Hµm of the oxide solid electrolyte coating on the diaphragm is 0.8µm~3µm; (4) The mass percentage (X%) of the oxide solid electrolyte in the positive electrode active material layer is 1%~3%; (5) The liquid retention coefficient Pg / Ah of the lithium-ion battery is 1.1g / Ah~1.7g / Ah.
[0009] Optionally, the fluorosulfonamide compound includes one or more of 1,1,1-trifluoro-N,N-dimethylmethanesulfonamide, dimethylaminosulfonyl fluoride, and N,N-diethylaminosulfonyl fluoride.
[0010] Optionally, the oxide solid electrolyte coating is applied to the surface of the separator near the positive electrode.
[0011] Optionally, the oxide solid electrolyte coating includes one or more of lithium aluminum titanium phosphate coating, lithium lanthanum zirconate coating, lithium aluminum germanium phosphate coating, and lithium lanthanum titanate coating.
[0012] Optionally, the oxide solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconate, lithium aluminum germanium phosphate, and lithium lanthanum titanate.
[0013] Optionally, the mass percentage of the positive electrode active material in the positive electrode active material layer is 85% to 98%.
[0014] Optionally, the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese oxide, lithium manganese iron phosphate, and lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li. 1+x Ni y Co z M (1-y-z) O2, where -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; where M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0015] The present invention provides an electrical device comprising the aforementioned lithium-ion battery.
[0016] This invention achieves synergistic performance by incorporating a solid oxide electrolyte (SSE) into the positive electrode and coating it with a separator, and introducing a fluorosulfonamide additive (first additive) and a mannitol carbonate sulfate additive (second additive) into the electrolyte. The performance is synergistic by precisely controlling the multidimensional relationship between the thickness of the SSE coating on at least one side of the separator, the content of the SSE in the positive electrode, the amount of electrolyte, and the ratio of the first and second additives. SSE can construct a low-temperature ion transport network and improve thermal stability and dendrite suppression, but the newly added interface can easily trigger high-temperature side reactions. The first additive forms a LiFSEI-rich film at the negative electrode to ensure safety, and the second additive forms a CEI film at the positive electrode to optimize high-temperature cycling; both have the problem of slightly increasing low-temperature impedance. SSE provides structural support, and the first and second additives specifically protect the positive and negative electrode interfaces, compensating for their respective defects. Furthermore, Equation 1: 0.8≤(H+X) / P≤8 can balance the ion conduction of oxide solid electrolytes and the amount of electrolyte used; Equation 2: 0.75≤(A+B) / (H+X)≤20 ensures that the additives fully cover the newly added interface of SSE; Equation 3: 0.16≤H / X≤6.43 can optimize the ion transport path; and Equation 4: 1.25≤A / B≤36 can balance the protection of positive and negative electrodes. This invention can achieve the optimal balance between high battery safety (excellent thermal shock performance), good low-temperature discharge characteristics, and high-temperature long-cycle stability, while reducing the amount of electrolyte used and improving the overall application value. Detailed Implementation
[0017] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0018] In the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0019] An embodiment of the present invention provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode includes a positive electrode active material layer, which comprises a positive electrode active material and an oxide solid electrolyte. At least one side of the separator is coated with an oxide solid electrolyte coating. The electrolyte includes a first additive and a second additive. The first additive includes a fluorosulfonylamine compound, and the second additive includes mannitol carbonate sulfate. The first additive has a mass percentage A% of 3%~45% in the electrolyte, the second additive has a mass percentage B% of 0.5%~5% in the electrolyte, the thickness Hµm of the oxide solid electrolyte coating on the separator is 0.5µm~5µm, the mass percentage X% of the oxide solid electrolyte in the positive electrode active material layer is 0.5%~5%, and the liquid retention coefficient Pg / Ah of the lithium-ion battery is 0.8g / Ah~2.5g / Ah. The lithium-ion battery satisfies the following relationship: Equation 1: 0.8 ≤ (H+X) / P ≤ 8; Equation 2: 0.75≤(A+B) / (H+X)≤20; Equation 3: 0.16 ≤ H / X ≤ 6.43; Equation 4: 1.25≤A / B≤36.
[0020] Specifically, by incorporating solid oxide electrolyte (SSE) into the positive electrode and coating it with a separator, and introducing fluorosulfonamide additives (first additive) and mannitol carbonate sulfate additives (second additive) into the electrolyte, synergistic performance is achieved through precise control of the multidimensional relationship between the thickness of the solid oxide electrolyte coating on at least one side of the separator, the content of solid oxide electrolyte in the positive electrode, the amount of electrolyte, and the ratio of the first and second additives. SSE can construct a low-temperature ion transport network and improve thermal stability and dendrite suppression ability, but the newly added interface is prone to causing high-temperature side reactions; the first additive forms a LiFSEI-rich film at the negative electrode to ensure safety, and the second additive forms a CEI film at the positive electrode to optimize high-temperature cycling, both of which have the problem of slightly increasing low-temperature impedance. SSE provides structural support, and the ratio of the first and second additives is specifically designed to protect the positive and negative electrode interfaces and compensate for their respective defects. Furthermore, Equation 1: 0.8≤(H+X) / P≤8 can balance the ion conduction of oxide solid electrolytes and the amount of electrolyte used; Equation 2: 0.75≤(A+B) / (H+X)≤20 ensures that the additives fully cover the newly added interface of SSE; Equation 3: 0.16≤H / X≤6.43 can optimize the ion transport path; and Equation 4: 1.25≤A / B≤36 can balance the protection of positive and negative electrodes. This invention can achieve the optimal balance between high battery safety (excellent thermal shock performance), good low-temperature discharge characteristics and high-temperature long-cycle stability, while reducing the amount of electrolyte used and improving the overall application value.
[0021] Incorporating solid oxide electrolyte (SSE) into the cathode and coating it with a separator can improve the low-temperature cycle performance and thermal safety of the battery. The SSE particles inside the cathode form a high-speed ion transport network, which effectively reduces the diffusion resistance of lithium ions inside the cathode at low temperatures, thereby improving the discharge capacity and rate performance at 0°C. At the same time, the SSE coating on the separator can enhance the thermal dimensional stability and mechanical strength of the separator, effectively suppressing lithium dendrite penetration and internal short circuits, thus exhibiting a higher thermal runaway initiation temperature and better safety. Mannitol carbonate sulfate additives primarily function at the cathode interface. The highly reactive disulfate functional groups in its molecules preferentially oxidize at the cathode interface, participating in the construction of a dense, lithium sulfonate-rich inorganic-organic composite cathode electrolyte interface (CEI) film. This film can extremely effectively inhibit the oxidative decomposition of the electrolyte on the cathode active surface under high voltage, the dissolution of transition metal ions, and oxygen release, fundamentally reducing heat sources and thus improving the thermal stability and high-temperature cycle life of the battery. At the same time, the decomposition products of carbonate functional groups (such as polycarbonate) endow the CEI film with good toughness and adhesion, which, together with the rigid framework formed by the sulfate, form a stable and ion-conducting protective layer.
[0022] In some embodiments, the lithium-ion battery satisfies at least one of the following relationships: Equation 5: 1≤(H+X) / P≤5.33; Equation 6: 1.67≤(A+B) / (H+X)≤15.67; Equation 7: 0.4 ≤ H / X ≤ 5; Equation 8: 1.5 ≤ A / B ≤ 30.
[0023] Specifically, the battery satisfies equations 5, 6, 7, and 8, and the synergistic effect of the first and second additives is better, which can improve the battery's high and low temperature cycle and thermal shock safety performance.
[0024] When (H+X) / P is low, the solid-state ion conduction path is insufficient, the electrolyte is relatively excessive, and the excessive amount of combustibles during thermal shock significantly increases the risk of thermal runaway. When (H+X) / P is high, the solid-solid contact interface impedance is too large, the electrolyte wetting is insufficient, ion transport is hindered at low temperatures, and the capacity utilization rate drops sharply. When (A+B) / (H+X) is low, the additive is insufficient to cover the large new interface of the oxide solid electrolyte. During high-temperature cycling, the electrolyte continues to decompose at the active interface, causing rapid capacity decay and impedance growth. When (A+B) / (H+X) is high, the decomposition products of the excessive additive form an excessively thick interface film, which seriously hinders lithium ion migration and leads to deterioration of low-temperature performance. When H / X is low, the membrane coating is too thin and cannot effectively uniform the ion flow, resulting in insufficient dendrite suppression and decreased thermal safety. When H / X is high, the membrane layer is too thick, reducing ion transport efficiency and significantly increasing internal resistance, thus affecting power characteristics. When the A / B ratio is low, the relative excess of B% leads to an excessively thick positive electrode interface film and excessively high low-temperature resistance. When the A / B ratio is high, the relative excess of A% leads to an excessively thick negative electrode SEI film, while insufficient positive electrode protection leads to accelerated dissolution of transition metals.
[0025] In some embodiments, the lithium-ion battery satisfies at least one of the following conditions: (1) The mass percentage A% of the first additive in the electrolyte is 10%~30%; (2) The mass percentage (B%) of the second additive in the electrolyte is 1% to 3%; (3) The thickness Hµm of the oxide solid electrolyte coating on the diaphragm is 0.8µm~3µm; (4) The mass percentage (X%) of the oxide solid electrolyte in the positive electrode active material layer is 1%~3%; (5) The liquid retention coefficient Pg / Ah of the lithium-ion battery is 1.1g / Ah~1.7g / Ah.
[0026] Specifically, the mass percentage A% of the first additive in the electrolyte includes, but is not limited to, 10%, 14%, 17%, 19%, 21%, 23%, 25%, 28%, and 30%. If A% is too low, the negative electrode interface protection is insufficient, and the dendrite suppression ability and acid capture effect decrease. If A% is too high, the excessively thick composite SEI film severely hinders ion migration and affects low-temperature performance. The mass percentage B% of the second additive in the electrolyte includes, but is not limited to, 1%, 1.5%, 1.8%, 2.1%, 2.4%, 2.7%, and 3%. If B% is too low, the positive electrode protection will be insufficient and the high-temperature cycle capacity retention rate will decrease. If B% is too high, the CEI film impedance will be too high, which will seriously restrict the low-temperature power characteristics. The thickness Hµm of the oxide solid electrolyte coating on the diaphragm includes, but is not limited to, 0.8µm, 1µm, 1.2µm, 1.5µm, 1.9µm, 2.3µm, 2.6µm, and 3µm. If Hµm is too low, the mechanical strength is insufficient and the resistance to dendrite penetration decreases. If Hµm is too high, the ion transport path is too long and the internal resistance increases significantly. The mass percentage of oxide solid electrolyte in the positive electrode active material layer, X%, includes but is not limited to 1%, 1.4%, 1.7%, 2%, 2.3%, 2.5%, 2.8%, and 3%. If X% is too low, the ion conduction pathway is insufficient; if X% is too high, the interfacial side reactions are aggravated, and the high-temperature cycling performance deteriorates. The electrolyte retention coefficient Pg / Ah of lithium-ion batteries includes, but is not limited to, 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah, 1.6g / Ah, and 1.7g / Ah. If Pg / Ah is too low, the electrolyte is severely insufficient, resulting in inadequate electrode wetting, breakage of ion transport channels, a surge in internal resistance, a sharp drop in capacity, and deterioration of low-temperature performance, leading to a drastic shortening of cycle life. If Pg / Ah is too high, the excess electrolyte acts as the main flammable material, significantly increasing the risk of thermal runaway.
[0027] In some embodiments, the fluorosulfonamide compound includes one or more of 1,1,1-trifluoro-N,N-dimethylmethanesulfonamide, dimethylaminosulfonyl fluoride, and N,N-diethylaminosulfonyl fluoride.
[0028] Specifically, the F functional group contained in the fluorosulfonamide compound molecule preferentially undergoes a reduction reaction on the negative electrode surface, forming a dense, stable, and LiF-rich solid electrolyte interphase (SEI) film. LiF has high stability, which can inhibit lithium dendrite growth, improve the safety threshold under battery thermal abuse conditions, and improve thermal shock performance. At the same time, the sulfonamide functional group (-S(=O)2N-) common to these compounds has a strong electron-withdrawing effect, which can preferentially capture free H in the electrolyte. + HF, purifying the interface environment, reduces erosion of the positive electrode structure; its decomposition produces Li x Products such as SOy and Li3N can further improve the ionic conductivity and mechanical stability of the interfacial film, thereby improving the high-temperature cycling performance of the battery.
[0029] In some embodiments, the oxide solid electrolyte coating is applied to the surface of the separator near the positive electrode.
[0030] Specifically, applying the oxide solid electrolyte coating to the surface of the separator near the positive electrode can effectively enhance the mechanical strength and thermal stability of the separator. However, applying the oxide solid electrolyte coating to the side of the separator facing the negative electrode can easily cause side effects.
[0031] In some embodiments, the oxide solid electrolyte coating includes one or more of lithium aluminum titanium phosphate coating, lithium lanthanum zirconate coating, lithium aluminum germanium phosphate coating, and lithium lanthanum titanate coating.
[0032] Specifically, this type of oxide solid electrolyte coating exhibits excellent thermal stability and high ion conduction efficiency. It can suppress lithium dendrite growth, optimize solid-liquid interface compatibility, reduce interface impedance, and enhance the mechanical properties of the separator, thereby significantly improving battery safety and electrochemical cycle stability.
[0033] In some embodiments, the oxide solid electrolyte includes one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconate, lithium aluminum germanium phosphate, and lithium lanthanum titanate.
[0034] Specifically, this type of oxide solid electrolyte exhibits excellent thermal stability and a highly efficient ion conduction network, which can suppress lithium dendrite growth and significantly improve battery safety and electrochemical performance.
[0035] In some embodiments, the mass percentage of the positive electrode active material in the positive electrode active material layer is 85% to 98%.
[0036] Specifically, the mass percentage of the positive electrode active material in the positive electrode active material layer includes, but is not limited to, 85%, 88%, 89%, 91%, 93%, 95%, 96%, and 98%. The positive electrode active material layer also includes a positive electrode conductive agent, a positive electrode binder, and a solvent. There is no limitation on the type of positive electrode conductive agent mentioned in this invention; any known conductive agent can be used. There is no limitation on the type of positive electrode binder mentioned in this invention; any known positive electrode binder can be used.
[0037] In some embodiments, the positive electrode active material includes one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese oxide, lithium manganese iron phosphate, and lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li. 1+x Ni y Co z M (1-y-z) O2, where -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; where M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0038] An embodiment of the present invention provides an electrical device including the lithium-ion battery described above.
[0039] For example, the aforementioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0040] The present invention will be further illustrated by the following examples.
[0041] Example 1 This embodiment illustrates a lithium-ion battery disclosed in this invention, including the following operating steps: Preparation of positive electrode Lithium cobalt oxide (LCO), acetylene black (SuperP), and polyvinylidene fluoride (PVDF) binder were mixed uniformly at a mass ratio of 97:1.5:1.5 and then uniformly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry 1. 1% (1% of the total mass of LATP oxide solid electrolyte, acetylene black (SuperP), and PVDF binder) was added to the positive electrode slurry 1 and uniformly dispersed to obtain positive electrode slurry 2. The mixed positive electrode slurry 2 was coated on both sides of an aluminum foil current collector, and then baked, rolled, and cut to obtain the positive electrode sheet.
[0042] Preparation of negative electrode Artificial graphite (anode active material), acetylene black (Super P) (anode conductive agent), CMC (thickener), and SBR (anode binder) (anode binder) are mixed evenly in a mass ratio of 94:2:1.2:2.8 and then evenly dispersed with deionized water to form a uniform anode slurry. The mixed slurry is coated on both sides of a copper foil current collector, and then baked, rolled, and cut into sheets to obtain the anode sheet.
[0043] Preparation of diaphragm A 2µm LATP coating is applied to one side of the diaphragm base membrane.
[0044] Preparation of electrolyte a. Mix ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP), and diethyl carbonate (DEC) in a mass ratio of 10:20:40:30 to form a mixed solvent. Remove water using a molecular sieve and set aside. Add 1M LiPF6 and mix thoroughly. b. Add 3% by mass of the first additive (1,1,1-trifluoro-N,N-dimethylmethanesulfonamide) and 2% by mass of the second additive (mannitol carbonate sulfate) to the colorless and transparent liquid obtained in step a to obtain the electrolyte.
[0045] Manufacturing of lithium-ion batteries The prepared positive electrode, separator, and negative electrode are stacked in sequence, with the separator in the middle of the positive and negative electrodes and the LATP coating facing the positive electrode. After winding and tab welding, a bare cell is obtained. The bare cell is placed in an aluminum-plastic film for liquid injection, encapsulation, etc., to obtain a lithium-ion battery.
[0046] Examples 2-32 and Examples 35-42 Examples 2-32 and Examples 35-42 are largely the same as Example 1, except that they use the parameters in Tables 1 and 2.
[0047] Example 33 Example 33 is similar to Example 1 in most steps, except that the first additive is dimethylaminosulfonyl fluoride.
[0048] Example 34 Example 34 is the same as Example 1 in most steps, except that the first additive is N,N-diethylaminosulfonyl fluoride.
[0049] Comparative Examples 1-11 and Comparative Examples 16-23 Comparative Examples 1-11 and Comparative Examples 16-23 are largely the same as those in Example 1, except that the parameters in Tables 1 and 2 are used.
[0050] Comparative Example 12 Comparative Example 12 is the same as Example 1 in most steps, except that the first additive is sulfonamide, which has the same single functional group as 1,1,1-trifluoro-N,N-dimethylmethanesulfonamide: sulfonamide group.
[0051] Comparative Example 13 Comparative Example 13 is the same as Example 1 in most steps, except that the first additive is fluoroethylene carbonate (FEC), which has the element F with 1,1,1-trifluoro-N,N-dimethylmethanesulfonamide.
[0052] Comparative Example 14 Comparative Example 14 is the same as Example 1 in most steps, except that the second additive is vinyl disulfate, which, like mannitol sulfate, contains two cyclic sulfates.
[0053] Comparative Example 15 Comparative Example 15 is the same as Example 1 in most steps, except that the second additive is ethylene carbonate, which has a single identical functional group as mannitol sulfate: carbonate group.
[0054] Table 1. Lithium-ion battery preparation parameters for the examples and comparative examples. Table 2. Lithium-ion battery preparation parameters for the examples and comparative examples. Performance testing The lithium-ion batteries prepared in the above embodiments and comparative examples were tested as follows.
[0055] Thermal shock test The lithium-ion batteries prepared in the above embodiments and comparative examples were charged at 25°C at a rate of 1C to the cutoff voltage and a cutoff current of 0.025C. They were then transferred to an oven and heated to 150°C at a rate of 5°C / min and kept constant for 60 minutes. The batteries were considered to have passed the test if they did not catch fire or explode. The number of battery cells tested was 20.
[0056] 45℃ Cyclic Performance Test The lithium-ion batteries prepared in the above embodiments and comparative examples were charged and discharged at 45°C at a rate of 1C / 1C within the charge and discharge cutoff voltage range. The discharge capacity of the first cycle was recorded as C1, and the discharge capacity of the Nth cycle was recorded as C2. The capacity of the Nth cycle was divided by the capacity of the first cycle to obtain the cycle capacity retention rate R2 = C2 / C1. The number of cycles of the lithium-ion battery when the cycle capacity retention rate R2 was 70% was recorded.
[0057] 0℃ Cyclic Performance Test The lithium-ion batteries prepared in the above embodiments and comparative examples were charged and discharged at 0°C at a rate of 1C / 1C within the charge and discharge cutoff voltage range. The discharge capacity of the first cycle was recorded as Y1, and the discharge capacity of the Nth cycle was recorded as Y2. The capacity of the Nth cycle was divided by the capacity of the first cycle to obtain the cycle capacity retention rate of the Nth cycle, X2 = Y2 / Y1. The cycle number of the lithium-ion battery when the cycle capacity retention rate X2 was 70% was recorded.
[0058] The test results are shown in Table 3.
[0059] Table 3 Performance test results of lithium-ion batteries prepared in the examples and comparative examples As can be seen from the test results in Table 3, compared with the test results of the examples, Comparative Example 1 has no additives and oxide solid electrolyte components, and only 1 needle puncture pass, resulting in a significant reduction in safety performance and a substantial decrease in high and low temperature cycle performance. This indicates that the lack of additives and oxide solid electrolyte leads to a reduction in the overall performance of the battery. The test results of Comparative Example 2-11 show that when A% is below 3%, lithium dendrite growth cannot be suppressed, significantly reducing thermal safety, causing severe corrosion of the cathode structure, and decreasing high-temperature cycling performance. When A% is above 45%, the excessively thick SEI film increases interfacial impedance, leading to a decrease in high and low temperature cycling performance. When B% is below 0.5%, it increases the oxidative decomposition of the cathode material under high voltage, the dissolution of transition metal ions, and oxygen release, worsening safety performance and high-temperature stability. When B% is above 5%, decomposition products (such as polycarbonate) increase the overall interfacial impedance, leading to a decrease in low-temperature cycling performance. When the thickness Hµm of the oxide solid electrolyte coating is below 0.5µm, the excessive thinness leads to a decrease in thermal stability and mechanical strength, a significant decrease in safety, and impaired ion transport. Low efficiency leads to decreased low-temperature cycling performance. When Hµm is higher than 5µm, the increased thickness increases the overall ion transport path length, resulting in increased ohmic polarization, making ion migration difficult at low temperatures and increasing the risk of side reactions with the electrolyte at high temperatures, thus reducing high and low temperature cycling performance. When the content of oxide solid electrolyte (SSE) X% is lower than 0.5%, the ion conductivity is low, and the low-temperature cycling performance decreases. When X% is higher than 5%, the contact between SSE and liquid electrolyte at high temperatures increases side reactions, exacerbates electrolyte consumption and impedance growth, and significantly reduces high-temperature cycling performance. When the liquid retention coefficient Pg / Ah is lower than 0.8g / Ah, the interfacial mass transfer rate is too low, and the low-temperature performance is significantly reduced. When Pg / Ah is higher than 2.5g / Ah, the amount of flammable material increases, and safety decreases. The test results of Comparative Examples 12-15 show that when the additive uses a single functional group substitute, it cannot suppress dendrite growth and high-voltage side reactions, resulting in low thermal shock safety performance and overall deterioration of battery performance. This indicates that the molecular structure of specific additives (such as the F element and sulfonamide group of fluorosulfonamide, and the disulfate and carbonate functional groups of mannitol carbonate) plays a key role in the construction of gradient interface films.
[0060] The test results of Comparative Examples 16-23 show that when (H+X) / P is higher than 8, the solid-solid interface impedance is too high, the electrolyte wetting is insufficient, and ion transport is hindered at low temperatures, leading to a sharp decline in low-temperature cycling performance. When (H+X) / P is lower than 0.8, excessive combustible material during thermal shock significantly increases the risk of thermal runaway and significantly reduces safety performance. When (A+B) / (H+X) is higher than 20, the interface film is too thick, hindering lithium-ion migration and affecting low-temperature cycling performance. When (A+B) / (H+X) is lower than 0.75, insufficient additives cause the electrolyte to continuously separate at the active interface during high-temperature cycling. The following are some possible causes: When H / X is higher than 6.43, the excessive thickness of the separator layer reduces ion transport efficiency and significantly increases internal resistance, leading to a decrease in cycle performance. When H / X is lower than 0.16, the separator coating is too thin and cannot effectively uniform ion flow, resulting in insufficient dendrite suppression and decreased thermal safety. When A / B is higher than 36, the relative excess of the first additive leads to an excessively thick SEI film on the negative electrode, while insufficient protection on the positive electrode exacerbates the dissolution of transition metals, resulting in a decrease in high-temperature cycle performance. When A / B is lower than 1.25, the relative excess of the second additive leads to an excessively thick interface film on the positive electrode, resulting in excessively high low-temperature impedance and a significant decrease in low-temperature cycle performance.
[0061] The test results of Examples 1-5 show that as the content A% of the first additive increases from 3% to 45%, the high interfacial properties of LiF effectively inhibit lithium dendrite growth, significantly improve thermal safety, and can capture free H+ in the electrolyte. + The addition of HF reduces the erosion of the positive electrode structure and improves high-temperature cycle performance. However, an excessively thick SEI film increases interfacial resistance, leading to a decrease in low-temperature cycle performance. When A% is in the range of 10%-30%, the overall performance of lithium-ion batteries is better.
[0062] The test results of Examples 6-10 show that as the content of the second additive B% increases from 0.5% to 5%, it can effectively suppress the oxidative decomposition of the cathode material, the dissolution of transition metal ions and the release of oxygen under high voltage, which has a positive effect on safety performance and high temperature stability. However, the decomposition products (such as polycarbonate) will increase the overall interfacial impedance and affect the low temperature cycle performance. When B% is in the range of 1%-3%, the overall performance of the lithium-ion battery is better.
[0063] The test results of Examples 11-15 show that as the thickness Hµm of the oxide solid electrolyte coating on the separator increases from 0.5µm to 5µm, the thermal stability (shrinkage resistance) and mechanical strength of the separator are significantly improved. It can effectively physically block dendrite penetration, improve safety performance, and provide additional lithium-ion transport channels, which is beneficial to improving low-temperature cycle performance. However, when the thickness is thicker, it will increase the overall ion transport path length, resulting in increased ohmic polarization, making ion migration difficult at low temperatures, and increasing the risk of side reactions with the electrolyte at high temperatures, leading to a decrease in cycle performance. When Hµm is in the range of 0.8µm-3µm, the overall performance of the lithium-ion battery is better.
[0064] The test results of Examples 16-20 show that as the content of oxide solid electrolyte (SSE) increases from 0.5% to 5%, it is beneficial to improve the positive electrode ion conductivity, improve the local heat generation at the positive electrode interface, and improve the low-temperature cycle performance. However, at high temperatures, the contact between SSE and liquid electrolyte will increase side reactions, aggravate electrolyte consumption and impedance growth, and reduce high-temperature cycle performance. When X% is in the range of 1%-3%, the overall performance of lithium-ion batteries is better.
[0065] The test results of Examples 21-25 show that as the electrolyte retention coefficient increases from 0.8 g / Ah to 2.5 g / Ah, the amount of electrolyte increases, which means an increase in flammable materials inside the battery. This significantly increases the risk of heat and gas generation during thermal shock and reduces safety. However, sufficient electrolyte can provide higher ionic conductivity and faster interfacial mass transfer rate at low temperatures, improving low-temperature performance. At high temperatures, sufficient electrolyte can buffer its consumption during long-term cycling and delay performance degradation, but too much electrolyte can also increase side reactions and affect high-temperature cycling performance. When Pg / Ah is in the range of 1.1 g / Ah-1.7 g / Ah, the overall performance of the lithium-ion battery is better.
[0066] The test results of Examples 26-32 show that when the type of oxide solid electrolyte and the oxide solid electrolyte coating of the separator are other types (LLZO, LAGP, LLTO), they have the same improvement effect on the battery.
[0067] The test results of Examples 33-34 show that when the first additive is replaced with other fluorosulfonyl amine compounds (dimethylaminosulfonyl fluoride, N,N-diethylaminosulfonyl fluoride), it has the same improvement effect on the battery.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A lithium-ion battery, characterized by, The lithium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material and an oxide solid electrolyte, at least one side surface of the separator is coated with an oxide solid electrolyte coating layer, and the electrolyte comprises a first additive and a second additive, the first additive comprises a fluorosulfonylamide compound, and the second additive comprises a mannitol carbonic acid sulfate ester. The mass percentage content A% of the first additive in the electrolyte is 3% to 45%, the mass percentage content B% of the second additive in the electrolyte is 0.5% to 5%, the thickness H of the oxide solid electrolyte coating layer on the separator is 0.5 to 5 microns, the mass percentage content X% of the oxide solid electrolyte in the positive electrode active material layer is 0.5% to 5%, and the liquid retention coefficient Pg / Ah of the lithium ion battery is 0.8 g / Ah to 2.5 g / Ah. The lithium ion battery satisfies the following relationship: Formula 1: 0.8≤(H+X) / P≤8; Formula 2: 0.75≤(A+B) / (H+X)≤20; Formula 3: 0.16≤H / X≤6.43; Formula 4: 1.25≤A / B≤36.
2. The lithium-ion battery of claim 1, wherein, The lithium ion battery satisfies at least one of the following relationships: Formula 5: 1≤(H+X) / P≤5.33; Formula 6: 1.67≤(A+B) / (H+X)≤15.67; Formula 7: 0.4≤H / X≤5; Formula 8: 1.5≤A / B≤30.
3. The lithium-ion battery of claim 1, wherein, The lithium ion battery satisfies at least one of the following conditions: (1) The mass percentage content A% of the first additive in the electrolyte is 10% to 30%; (2) The mass percentage content B% of the second additive in the electrolyte is 1% to 3%; (3) The thickness H of the oxide solid electrolyte coating layer on the separator is 0.8 to 3 microns; (4) The mass percentage content X% of the oxide solid electrolyte in the positive electrode active material layer is 1% to 3%; (5) The liquid retention coefficient Pg / Ah of the lithium ion battery is 1.1 g / Ah to 1.7 g / Ah.
4. The lithium-ion battery of claim 1, wherein, The fluorosulfonylamide compound comprises one or more of 1,1,1-trifluoro-N,N-dimethylmethanesulfonamide, dimethylsulfamoyl fluoride and N,N-diethylsulfamoyl fluoride.
5. The lithium-ion battery of claim 1, wherein, The oxide solid electrolyte coating layer is coated on the surface of the separator close to the positive electrode.
6. The lithium-ion battery of claim 1, wherein, The oxide solid electrolyte coating layer comprises one or more of a lithium titanium aluminum phosphate coating layer, a lithium lanthanum zirconate coating layer, a lithium aluminum germanium phosphate coating layer and a lithium lanthanum titanate coating layer.
7. The lithium-ion battery of claim 1, wherein, The oxide solid electrolyte comprises one or more of lithium titanium aluminum phosphate, lithium lanthanum zirconate, lithium aluminum germanium phosphate and lithium lanthanum titanate.
8. The lithium-ion battery of claim 1, wherein, The mass percentage content of the positive electrode active material in the positive electrode active material layer is 85% to 98%.
9. The lithium-ion battery of claim 1, wherein, The positive electrode active material comprises one or more of transition metal lithium oxides, lithium iron phosphate, lithium manganate, lithium manganese iron phosphate, lithium vanadium phosphate; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is selected from one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, Zr.
10. An electrical device, characterized by The lithium ion battery comprises the lithium ion battery according to any one of claims 1 to 9.
Citation Information
Cited By
Lithium ion battery and electric device
CN121964786A
Lithium ion battery and electric device using the same
CN121964786B
